The Protective Effects of Curcuminand Caffeic acid alone or in combination onNicotine-induced Lung Injury in Rats - Sylvia A. Boshra (International Journal of Phytomedicine, 2016)
The present study was performed to explore the protective effects ofcaffeic acid (20 mg/kg.bw) and curcumin (50mg/k.g.b.w.) on nicotine-induced lung injury alone and in combination.Their effect was compared to N-acetylcysteine (500mg/k.g.b.w.) as known modulator of oxidative stress. Nicotine treatment (0.6mg/kg/day, i.p, for 21 consecutivedays) resulted in a significantincrease (p<0.05) in plasmaalanine aminotransferase (ALT), aspartate aminotransferase (AST), lactate dehydrogenase (LDH), total cholesterol (TC), triglycerides (TG), low density lipoprotein cholesterol (LDL-C) and well as plasma and lung thiobarbituric acid reactive substances (TBARS), nitric oxide(NO) and tumor necroses factor-α (TNF-α) concomitant with significant decline in non-enzymatic antioxidant like reduced glutathione(GSH) and in enzymatic antioxidants like catalase (CAT) andsuperoxide dismutase (SOD) as well as high density lipoprotein cholesterol (HDL-C). Furthermore, nicotine treatment caused severe injury indicated bythe histopathological examination of lung tissue compared to normal control group. Oral treatment with caffeic acid alone orcurcuminalone or in combination as well as N-acetylcysteine alone prevented the elevation in plasma ALT, AST, LDH,TC, TG, LDL-C, NO, TNF-α and TBARSlevels concomitant with an increments in the HDL-C, reduced glutathione GSH and antioxidant enzymes (CAT and SOD) and amelioration inhistopathological changes and injury induced by nicotine. Lung protection was prominent in curcuminand N-acetylcysteine alone more than caffeic acid alone or caffeic acid and curcuminin combination. Moreover, curcumin has the potential to be used in a combination therapy with caffeic acid, with decreasing the therapeutic dose of caffeic acid and therefore its side-effects.